The role of the cytoskeleton in fibrotic diseases - Niu, Caoyuan; Hu, Yanan; Xu, Kai; Pan, Xiaoyue; Wang, Lan; Yu, Guoying (Frontiers in Cell and Developmental Biology, 2024)
Fibrosis is the process whereby cells at a damaged site are transformed into fibrotic tissue, comprising fibroblasts and an extracellular matrix rich in collagen and fibronectin, following damage to organs or tissues that exceeds their repair capacity. Depending on the affected organs or tissues, fibrosis can be classified into types such as pulmonary fibrosis, hepatic fibrosis, renal fibrosis, and cardiac fibrosis. The primary pathological features of fibrotic diseases include recurrent damage to normal cells and the abnormal activation of fibroblasts, leading to excessive deposition of extracellular matrix and collagen in the intercellular spaces. However, the etiology of certain specific fibrotic diseases remains unclear. Recent research increasingly suggests that the cytoskeleton plays a significant role in fibrotic diseases, with structural changes in the cytoskeleton potentially influencing the progression of organ fibrosis. This review examines cytoskeletal remodeling and its impact on the transformation or activation of normal tissue cells during fibrosis, potentially offering important insights into the etiology and therapeutic strategies for fibrotic diseases.